Healthy Family Indicator in Barombong Village Tamalate District Makassar City - Aripa, Lusyana; Hoda, Ferdinandus Suban; Mahoklory, Serly Sani; Lewar, Emanuel Suban Bala; Suharto, Suharto; Umar, Risa Bernadip; Sahalessy, Yona Camelia; Nursinah, Andi (International Journal of Health Sciences, 2023)
The government created the Healthy Family Indicators (IKS) program to assess or measure the level of progress of healthy families in each region. The Healthy Family Index (IKS) is a calculation of the twelve healthy family indicators for each family whose size ranges from 0 to 1. Families classified as healthy families are families with IKS > 0.8. IKS achievements are still relatively low for several regions in Indonesia, the results of IKS calculations from the 9 initial target provinces namely North Sumatra, South Sumatra, Lampung, DKI Jakarta, West Java, Central Java, East Java, Banten and South Sulawesi as of June 8 2017 obtained families who have IKS above 0.8 of 0.163 out of 570,326 families (Pusdatin, 2018). This study aims to describe the family indicators and index of healthy families in Barombong Village. The type of research used is quantitative descriptive research. Based on the results of the study showed that the healthy family index of 95 families consisted of 32 (33.7%) healthy families, 27 (28.4%) pre-healthy families and 36 (37.9%) unhealthy families. Meanwhile, 62 families (69.7%) participated in the Family Planning program, 6 families (75%) gave birth to mothers, 5 families (83.3%) babies received complete basic immunization, babies received exclusive breastfeeding there were 5 families (55.6%), Toddlers who received growth monitoring there were 10 families (62.5%), there were no pulmonary TB sufferers in 95 families (100%), Patients with hypertension who received regular treatment there were 3 families (50%) ), no mental disorders were found in 95 families (100%), 68 families (71.6%) smoked family members, 75 families (78.9%) had become JKN members, 95 families (100%) these already have clean water facilities, and 95 families (100%) already use healthy latrines. It is recommended that the local puskesmas make policies and efforts to increase family planning participation so that couples of reproductive age (PUS) realize that participating in family planning is to limit birth rates in the long term, make regulations and make appeals not to smoke, especially for areas that are close to members' activities. family.